FENOMENA SELF HEALING UNTUK PENGHILANG STRES SEBAGAI PROMOSI PARIWISATA MELALUI DESTINASI HIDDEN GEM JUNGGLE MILK LEMBANG - Superwiratni, Superwiratni; Yayan Sugiarto (Juremi: Jurnal Riset Ekonomi, 2024)
Selft Healing itself is currently used by young people to get out of the fatigue of the mind, daily problems from the pile of tasks and work problems to go on a trip abroad, to the shopping center, to the streets, to the beach, to the mountains or just to eat at a restaurant with a soothing view or to go to places called hidden gems to find calm. In this study, there is more focus on, first, "Selft healing" is included in the type of emotion-focused strategy that is conscious adjustment. Second, "Selft healing" activities are carried out in the form of fun activities and bring tranquility such as nature tourism, culinary tourism, cultural tourism and special interest tourism and are uploded to social media so that it becomes one of the promotion strategies of a destination. The data analysis technique used is qualitative analysis. The achievement target in this study is published in the national accreditation journal Sinta 3. The TKT that will be produced is at level 2 because this research can answer the research hypothesis, the research instrument, and the research design have been explored